Smallholder farmers engage government: the Kenya National Farmers Federation at work - Nyando, Violet (Technical Centre for Agricultural and Rural Cooperation, 2018)
The Kenya National Farmers Federation has implemented an EU-funded food security project aimed at building up the policy dialogue capacity of Kenyan farmers. The federation has facilitated the participation of all agricultural sector actors in policy development and implementation, to improve government support towards agricultural sector growth and development.